Dampak Pendapatan Usaha Kecil Menengah terhadap Kesejahteraan Pekerja dalam Perspektif Ekonomi Syariah: Studi Pekerja Perempuan Tape Singkong Desa Pordapor Kecamatan Guluk-Guluk - Liaqodatul mahmudah; Anna Zakiyah Hastriana (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
In order to fulfill life's needs in order to be prosperous, people who have the ability and are keen to see their own potential and are able to identify the environment, can find opportunities and open up business opportunities for the community. Businesses undertaken to meet living needs include Micro, Small and Medium Enterprises. The problem in this research is an economic problem that has become problematic in people's lives, namely related to increasing welfare, so in this research we will discuss the impact of MSMEs on improving people's welfare.this research  is entitled the role of micro.small and medium enterprises in improving community welfare according to on islamic perspective. Case study of Cassava Tape in Pordapor Village, Guluk-Guluk District. This research will discuss the role of Cassava Tape Business in improving community welfare. And discusses the role of the Cassava Tape business in improving community welfare according to an islamic perspective. To answer the questions above. This research uses qualitative reseanch,white the data collecton technique emphasizes interviews with 15 female workers in cassava tape in Pordapor village, Guluk-guluk subdistrict.